Enhancing Basketball Chest Pass Skills Through Teaching At The Right Level Approach - Reswaya, Aniesa; Syamsuramel; Yusaromi, Armando (JURNAL PENJAKORA, 2025)
Finding out if the Teaching at The Right Level (TaRL) approach enhances learning results in basketball games where players practice the chest pass at State Junior High School 35 Palembang is the aim of this study. This class action (PTK) inquiry used two action cycles. Learning activities (attitudes), cognitive tests (knowledge), and performance tests (skills) are the research instruments. This method of gathering data uses written tests, documentation, and observation.Test data analysis makes advantage of learning completeness.The study's subjects were thirty-one eighth-grade students. According to the research's findings and discussion, the first cycle's findings showed that the student skill test's percentage of completeness was 70.97% with an average score of 74.19%, and the knowledge assessment's percentage of completeness was 67.74% with an average score of 78.71. The completion percentage of the student learning activity assessment was 70.77%, with an average of 70.77. The results of the student knowledge assessment with a percentage of completeness reached 93.55% with an average score of 85.48 in the second cycle, while the results of the student skill test with completeness reached 83.87% with an average score of 91.40.  With an average score of 84.07, the evaluation of students' learning activity achieved 84.07%. Based on this information, it can be said that State Junior High School 35 Palembang's basketball game chest passes are successfully learned with the implementation of the Teaching at The Right Level (TaRL) approach